Use of aspirin for primary and secondary prevention of cardiovascular disease in diabetic patients in an ambulatory care setting in Spain - Fernández-de-Bobadilla Jaime; Rejas-Gutiérrez Javier; Navarro-Artieda Ruth; Sicras-Mainar Antoni; Frías-Garrido Xavier; Ruiz-Riera Rafael (BMC Family Practice, 2007)
Abstract Background This study was conducted in order to determine the use of aspirin and to assess the achievement of therapeutic targets in diabetic patients according to primary (PP) or secondary prevention (SP). Methods This is a retrospective, observational study including patients ≥18 years with diabetes mellitus followed in four primary care centers. Measurements included demographics, use of aspirin and/or anticoagulant drugs, co-morbidities, clinical parameters and proportion of patient at therapeutic target (TT). Descriptive statistics, chi-square test and logistic regression model were used for significance. Results A total of 4,140 patients were analyzed, 79.1% (95% confidence intervals [CI]: 77.7–80.5%) in PP and 20.9% (95% CI: 18.2–23.7%) in SP. Mean age was 64.1 (13.8) years, and 49.3% of patient were men (PP: 46.3, SP: 60.7, p = 0.001). Aspirin was prescribed routinely in 20.8% (95% CI: 19.4–22.2%) in PP and 60.8% (95% CI: 57.6–64.0%) in SP. Proportion of patient at TT was 48.0% for blood pressure and 59.8% for cholesterol. Use of aspirin was associated to increased age [OR = 1.01 (95% CI: 1.00–1.02); p = 0.011], cardiovascular-risk factors [OR = 1.14 (95% CI: 1.03–1.27); p = 0.013], LDL-C [OR = 1.42 (95% CI: 1.06–1.88); p = 0.017] and higher glycated hemoglobin [OR = 1.51 (95% CI: 1.22–1.89); p = 0.000] were covariates associated to the use of aspirin in PP. Conclusion Treatment with aspirin is underused for PP in patients with diabetes mellitus in Primary Care. Achievement of TT should be improved.